Pengaruh Electronic Word Of Mouth (eWOM) Dan Iklan Melalui YouTube Terhadap Minat Beli Skin Pada Game Online Mobile Legends: Bang Bang di Kabupaten Karawang Tahun 2022 - Fery Ryansyah Putra; Endang Taufiqurahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to identify, analyze and explain the effect of Electronic Word of Mouth (eWOM) and YouTube Advertising on Interest in Buying Skins in the online game Mobile Legends: Bang Bang in Karawang Regency. This study uses a quantitative method with a descriptive and verification approach. With a sample of 347 respondents taken from the Karawang Mobile Legends Community population consisting of 2,579 people using a non-probability sampling technique. As well as using path analysis and hypothesis testing using the t test and f test. By using Microsoft Excel tools, Method of Successive Interval (MSI), and the SPSS application version 25. Based on the results of the analysis that has been carried out in this study, it proves that electronic word of mouth images, YouTube advertising and interest in buying skins in the online game Mobile Legends in Karawang Regency are included in the good category. The correlation coefficient between the variables Electronic Word of Mouth and YouTube Advertising obtained a value of 0.719 which means that it has a strong, positive and significant correlation level between Electronic Word of Mouth and YouTube Advertising. The partial influence of Electronic Word of Mouth on Buying Interest is 35.8% greater than YouTube Advertising which is 26.6%. So it can be stated that Electronic Word of Mouth contributes more to Buying Interest compared to YouTube Advertising. The simultaneous effect of Electronic Word of Mouth and YouTube Advertising on Buying Interest is 62.4% while the remaining 37.6% is another variable not examined in this study.